Volunteer work and a course in developing leadership skills for school students In Al-Tayyeba and Al-Wasatia Brigades; Irbid Governorate - alshraiedah, Bushra waleed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to real the role of voluntary work in the development of leadership skills among school students in the directorate of education of Al-Tayyeba and Al-Wasatia Also, This study relied on the descriptive survey method. Moreover, The study population consisted of (4052) male and female students from the eighth, ninth and tenth grades. The sample of the study was chosen by stratified random stratified method representing the study population, The sample of the study was (413) male and female students, The study used the questionnaire as a tool for the study to reach its goals; statistical program (SPSS) was used to process data statistically. Furthermore, The results of the study showed that The role of voluntary work in developing leadership skills among school came largely As the study recommended, to allocate a student project concerned with volunteering for each student in the basic stage in the service of society, and to strengthen the partnership between the Ministry of Education and the Ministry of Social Development.